Analyzing numeracy skills of upper primary graders in real-world problem contexts - Akmal, Nurul; Idris, Khairiani; Fauziana, Fauziana; Harun, Jamilah (Fakultas Tarbiyah Universitas Ibrahimy, 2025)
Numeracy skill is a critical skill for elementary school students, enabling them to apply mathematical concepts in everyday contexts and make informed decisions. This study investigates the numeracy skills of 55 fifth-grade students from Lhokseumawe City, Aceh Province. The students’ numeracy skills were measured across three key indicators: counting, numerical relations, and arithmetic operations. A descriptive quantitative approach was used to assess students' abilities. The results indicated that while students performed well in basic counting and arithmetic tasks, they struggled with tasks involving numerical relations and distinguishing quantities. The highest performance was observed in